A Guideline for Achieving the Best Electrical Performance with Strategy of Halo in Graphene Nanoribbon Field Effect Transistor. (18th October 2016) - Eshkalak, Maedeh Akbari; Anvarifard, Mohammad K.
Abstract : In this paper, for the first time, we present a useful guideline with halo strategy for Graphene Nanoribbon Field Effect Transistors (GNRFET) to obtain the best electrical performance. The Non-Equilibrium Green's Function (NEGF) method is used to solve the Schrödinger equation self-consistently with the two-dimensional (2D) Poisson equation under the ballistic transport. We compare the figure of merits of the three GNRFET structures, which are conventional GNRFET (C-CNTFET), single-halo GNRFET (SH-GNRFET) and double-halo GNRFET (DH-GNRFET). The results revel that the DH-GNRFET significantly decreases the leakage current as compared to two other structures and also the SH-GNRFET gets the highest ratio of ION /IOFF . Furthermore, we benefit from a two dimensional 'top-of-the-barrier' approach under ballistic transport to study other main characteristics of GNRFETs. The extracted results by this approach show that the SH-GNRFET provides a smaller quantum capacitance, small gate capacitance, and lower switching delay time as compared to the DH-GNRFET.